How Will LITHOPROBE's Final Chapter Be Written? - Percival, John; Lucas, Stephen; Jones, Alan; Beaumont, Christopher; Eaton, David; Rivers, Toby (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1999)
Summary Fifteen years after pioneering a program of integrated research in the earth sciences, LITHOPROBE faces the challenge of assembling and integrating results acquired in ten transects across the Canadian landmass that have sampled four billion years of Earth history. Beyond the data legacy that LITHO-PROBE will leave, a global synthesis is planned that will serve as a comprehensive conceptual framework for the structure and evolution of the continental crust. A Pan-LITHOPROBE subcommittee, formed to provide guidance through the synthesis process, is proposing that LITHOPROBE insights be used to address current thematic issues of global relevance and interest. To obtain broad input to the synthesis, LITHOPROBE will sponsor a series of thematic workshops on topics including: Variations and Styles of Tectonic Processes through Space and Time; Crustal Growth, Preservation and Recycling; Magmatic, Metamï ö hie and Tectonic Processes; and Lower Crust, Moho and Mantle Lithosphère. Each workshop will yield a LITHOPROBE report and initiate work on formal publication volumes. We solicit suggestions for additional unifying themes.